Model Of Adoption And Sustainability Of E-Wallet Use Of Dana, OVO, And Gopay In Surakarta City: A Technology Acceptance Model Approach - Septana Wulandari; Rochman Hadi Mustofa (UNIVED Press, 2025)
The rapid development of technology in Indonesia has brought great changes in many aspects of life, one of which is financial technology. The rapid advancement of technology can help many sectors, one of which is the Indonesian financial industry. This study aims to evaluate the structural model of adoption of e-wallet use by utilizing the Technology Acceptance Model theory among the people of Surakarta City. The research method used is quantitative through questionnaire distribution. The sampling technique used was purposive sampling, and the data was examined through the Partial Least Squares (PLS) method in Structural Equation Modeling (SEM) analysis. The results of the study explained that the structural model developed in this study is feasible to be used as an instrument for measuring the factors that influence a person to adopt an e-wallet.